2012
DOI: 10.3389/fphys.2011.00116
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between DNA Methylation and Phenotypic Plasticity in Invertebrates?

Abstract: There is a significant amount of variation in DNA methylation characteristics across organisms. Likewise, the biological role of DNA methylation varies across taxonomic lineages. The complexity of DNA methylation patterns in invertebrates has only recently begun to be characterized in-depth. In some invertebrate species that have been examined to date, methylated DNA is found primarily within coding regions and patterning is closely associated with gene function. Here we provide a perspective on the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
146
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 34 publications
(49 reference statements)
15
146
1
Order By: Relevance
“…Using samples generated in a reciprocal transplant experiment conducted in the field on the Great Barrier Reef, these investigators identified correlations of differential gene expression and DNA methylation in corals across populations, and between the outplant environments that varied in abiotic conditions. In addition to assessing the relationship of gene expression to gene methylation, the study also revealed a pattern where weak methylation increased the flexibility, or plasticity of gene expression, in response to environmental cues, something that had been proposed earlier by other investigators (Roberts and Gavery, 2012). Studies such as that conducted by Dixon and colleagues will begin to reveal how and whether epigenetic mechanisms operate in natural populations to support phenotypic plasticity.…”
Section: Pioneering Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Using samples generated in a reciprocal transplant experiment conducted in the field on the Great Barrier Reef, these investigators identified correlations of differential gene expression and DNA methylation in corals across populations, and between the outplant environments that varied in abiotic conditions. In addition to assessing the relationship of gene expression to gene methylation, the study also revealed a pattern where weak methylation increased the flexibility, or plasticity of gene expression, in response to environmental cues, something that had been proposed earlier by other investigators (Roberts and Gavery, 2012). Studies such as that conducted by Dixon and colleagues will begin to reveal how and whether epigenetic mechanisms operate in natural populations to support phenotypic plasticity.…”
Section: Pioneering Studiesmentioning
confidence: 80%
“…Although the level of organismal response can vary (Reusch, 2014;Sunday et al, 2014), phenotypic plasticity has emerged as an important area of study as it occurs on ecological rather than evolutionary time scales (i.e., more rapidly than evolutionary adaptation). Recently, there has been an emergence of studies exploring how epigenetic and epigenomic mechanisms might contribute to phenotypic plasticity in marine metazoans (Roberts and Gavery, 2012;Ledón-Rettig, 2013;Schrey et al, 2013;Dixon et al, 2014;Metzger and Schulte, 2016). Here, epigenetic modifications of DNA, such as DNA methylation, regulate and/or change gene expression, and thus change the transcriptome without changing DNA sequence (Szulwach and Jin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to a lack of recognizable Dnmt-like genes and limited DNA methylation patterns in several well-studied model systems (Suzuki & Bird, 2008;Roberts & Gavery, 2012). For example, the worm Caenorhabditis elegans essentially lacks DNA methylation, and there is no transposable element methylation in the honeybee, Apis mellifera (Simpson et al, 1986;Wang et al, 2006).…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 99%
“…DNA methylation, which typically involves the addition of a methyl group to cytosine within CpG dinucleotides in animals, is perhaps the most extensively characterized epigenetic mechanism in eukaryotes (Jones, 2012). Although DNA methylation has been found in many clades, its pattern and genomic distribution vary widely, suggesting that it may have diverse functions and different modes of targeting specific DNA elements in different taxa (Roberts & Gavery, 2012;Sch€ ubeler, 2015). Both histone post-translational modification (PTM) and small RNA regulation can impact gene expression but occur through different mechanisms (Lowdon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These key molecular signatures are as follows: (i) little molecular differentiation between phenotypes in transcription but subtle nonrandom differentiation at the transcriptional network level; (ii) no evidence of a role for DNA methylation or miRNAs in regulating phenotypic differentiation and an overall lack of distinct methylome patterning, together with evidence of methylation turnover; and (iii) a similar role for both conserved toolkit genes and previously unidentified taxonomically restricted genes in phenotypic differentiation. These characteristics may allow plasticity in the regulation of the genome, and thus facilitate plasticity at the phenotypic level (52). The sequencing of more species with different levels of plasticity and multiple phenotypes will be required to confirm this hypothesis (6).…”
Section: Discussionmentioning
confidence: 99%